Analyticity constraints for hadron amplitudes: Going high to heal low-energy issues. (27th June 2018) - Mathieu, V.; Nys, J.; Pilloni, A.; Fernández-Ramírez, C.; Jackura, A.; Mikhasenko, M.; Pauk, V.; Szczepaniak, A. P.; Fox, G.
Abstract: Analyticity constitutes a rigid constraint on hadron scattering amplitudes. This property is used to relate models in different energy regimes. Using meson photoproduction as a benchmark, we show how to test contemporary low-energy models directly against high-energy data. This method pinpoints deficiencies of the models and treads a path to further improvement. The implementation of this technique enables one to produce more stable and reliable partial waves for future use in hadron spectroscopy and new physics searches.